Pregabalin-induced urticarial rash and neutropenia in a renal transplant recipient: a case report - Sanjeev Sahota; Robin Geoffrey Parry; Giorgio Gentile (BMC Nephrology, 2019)
Abstract Background Pregabalin is a medication used to treat epilepsy, neuropathic pain and generalised anxiety disorder. The most common side effects of pregabalin include dizziness, drowsiness, weight gain, ataxia and diplopia. On the other hand, neutropenia and rash are rare side effects of pregabalin, and at the time of writing, there are only two documented cases of neutropenia and one of rash in the literature, none of which involved renal transplant recipients. Case presentation We present a 37-year-old renal transplant recipient who was admitted with lethargy, sore throat, urticarial rash and neutropenia after recently being commenced on pregabalin. On physical examination, he had erythematous urticarial rash near his renal transplant scar, on his right elbow, left knee and left wrist. Bacterial/viral serology and immunology were all negative. A blood film confirmed neutropenia and revealed reactive lymphocytes and neutrophil left shift, and those features were compatible with drug reaction. After cessation of the pregabalin, the neutropenia resolved. No other causes of neutropenia or urticarial rash were identified. Conclusion To the best of our knowledge, we have described the first case of concomitant pregabalin-induced neutropenia and urticarial rash in a kidney transplant patient. This case report highlights the importance of close monitoring when starting any new medications, particularly in the immunosuppressed population, and is relevant because of the growing usage of pregabalin for treating neuropathic pain in such patients and the risk that a missed pregabalin-related neutropenia could lead to unnecessary modifications of the immunosuppressive treatment.